PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL UNTUK MENGUJI PERSEPSI RESIKO ADOPSI E-BANKING - Edy Purwo Saputro (Benefit Jurnal Manajemen dan Bisnis, 2013)
The purpose of this paper is to identify risk factors that discourage consumers from adopting e-banking services. Perceived risk is a key construct in consumer decision making, whereas whether this is true in e-banking market is rarely researched. An exploration of this dynamic market is therefore critical to develop theoretical and practical implications. The investigation uses quantitative research methods. Primary data were collected by self-administered questionnaires containing 200 respondents are analysed through structural equation modelling. Results indicate that the concept of perceived risk has merit in explaining consumers’ decisions on whether to use e-banking.